Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/microorganisms8030377
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Cost of blaNDM-5-Carrying p3R-IncX3 Plasmids in Wild-Type NDM-Free Enterobacteriaceae

Abstract: The wide dissemination of New Delhi metallo-β-lactamase genes (blaNDM) has resulted in the treatment failure of most available β-lactam antibiotics, with IncX3-type blaNDM-5-carrying plasmids recognised as having spread worldwide. In China, bacteria carrying these plasmids are increasingly being detected from diverse samples, including hospitals, communities, livestock and poultry, and the environment, suggesting that IncX3 plasmids are becoming a vital vehicle for blaNDM dissemination. To elucidate the fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…10,20 The rapid spread of bla NDM may in part be due to the limited fitness cost conferred by this enzyme to its bacterial hosts. 21,22 Among MBL enzymes NDM is the most common in Enterobacterales; a study conducted using isolates from 40 countries between 2012 and 2014 revealed that 44.2% of all MBL-producing Enterobacterales possessed bla NDM , 39.3% harbored bla VIM , and 16.5% contained bla IMP . 11 K. pneumoniae, followed by E. coli, are the most common hosts of bla NDM across global surveillance studies.…”
Section: Introductionmentioning
confidence: 99%
“…10,20 The rapid spread of bla NDM may in part be due to the limited fitness cost conferred by this enzyme to its bacterial hosts. 21,22 Among MBL enzymes NDM is the most common in Enterobacterales; a study conducted using isolates from 40 countries between 2012 and 2014 revealed that 44.2% of all MBL-producing Enterobacterales possessed bla NDM , 39.3% harbored bla VIM , and 16.5% contained bla IMP . 11 K. pneumoniae, followed by E. coli, are the most common hosts of bla NDM across global surveillance studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of antibiotic pressure, the presence of resistance genes in plasmids will impose fitness costs on their host [ 12 ]. However, a recent in vitro study has shown that up to 75.9% (22/29) Enterobacteriaceae strains did not produce fitness costs after obtaining the IncX3 plasmid through conjugation test [ 13 ], which may facilitate the dissemination of the plasmid. Genomic islands are clusters of genes of probable horizontal origin in bacterial or archaeal genomes.…”
mentioning
confidence: 99%
“…On a broader perspective, our results warrant further research on plasmid-evolutionary dynamics in different E. coli lineages and sub-lineages to better understand why some of them appear to be more prone to acquire and maintain MDR plasmids [6, 47]. Available data support that plasmids of clinical origins rarely reduce fitness of clinical host strains [29, 30, 45, 4951] to the extent often seen in the pioneering studies of plasmid-host compensatory evolution [10, 20, 22, 52]. It is also clear that this alone cannot explain how successful clone-plasmid associations emerge.…”
Section: Discussionmentioning
confidence: 83%